PESAN-PESAN MORAL DALAM PISAAN DAN WAYAK - ., Muntazir (JURNAL PESONA, 2016)
Through mass media, literture can be enjoyed both in spoken literture and written literature. One of litertures which can be expressed orally is poetry. In this study, the researcher tried to understand the moral messages of Lampung poetry, in nature aspect and language methode. The Lampung poetry choosen is âPisaanâwhich originally from Way Kanan and âWayakâ from Liwa. Both of them are included in Lampung Pesisir. The data analysis were focused on the from of Pisaan and Wayak poetry which were analysed based on the moral messages that included physical structure meaning and internal structure meaning.Keywords: Moral Message, Poetry, Pisaan, Wayak, Lampung.